2013
DOI: 10.1007/s10620-013-2750-6
|View full text |Cite
|
Sign up to set email alerts
|

Rapid On-Site Evaluation Reduces Needle Passes in Endoscopic Ultrasound-Guided Fine-Needle Aspiration for Solid Pancreatic Lesions: A Risk–Benefit Analysis

Abstract: Variable sampling policies using ROSE generally achieve greater per-case adequacy with fewer needle passes than non-ROSE sampling policies using a fixed number of passes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 21 publications
0
34
0
2
Order By: Relevance
“…Studies have shown considerable variability in the benefits of ROSE, partly due to the adequacy rate of the sampler (i.e., the person performing the biopsy procedure) [1, 24-26]. ROSE provides little benefit when samplers have high adequacy rates [1, 27, 28], and variation in adequacy can be explained by experience [29, 30].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown considerable variability in the benefits of ROSE, partly due to the adequacy rate of the sampler (i.e., the person performing the biopsy procedure) [1, 24-26]. ROSE provides little benefit when samplers have high adequacy rates [1, 27, 28], and variation in adequacy can be explained by experience [29, 30].…”
Section: Discussionmentioning
confidence: 99%
“…There is no doubt that ROSE not only increases the overall diagnostic yield, but also effectively helps to triage the specimen for ancillary studies [40,41,42]. The value of ROSE is particularly more significant for deep-seated lymphomas than for other nonhematopoietic or superficial lesions.…”
Section: Fna Diagnosis Of Deep-seated Lymphomas Via Eus/ebus Emphasimentioning
confidence: 99%
“…Multiple studies have shown that ROSE increases diagnostic yield by about 10% to 15% [7,8]. ROSE has also been shown to reduce the number of needle passes performed [9]. Due to proximity to vital structures, risk of complications such as bleeding, and time, fewer needle passes may be beneficial.…”
mentioning
confidence: 99%